Internet of Things Implementation for Train Tracking Information (Case Study: UK and Indonesia) - Panjaitan, Hanna; Priyanto, Sigit; Dewanti, Dewanti; Kemp, Adrew H. (Universitas Ibn Khaldun Bogor, 2024)
The Internet of Things (IoT) has revolutionized information gathering and daily activities, particularly in train operations. However, the implementation of IoT in Indonesia has not been optimally used, leading to delays in train location information. This research aims to explore the application of IoT for train location tracking systems in two countries, namely the UK as a developed country that adopts technology more quickly compared to Indonesia. This study employs qualitative methods with case studies approach to analyze IoT implementation in train tracking in Indonesia and the UK, focusing on regulations, and technology which support train tracking systems. Several research has discussed about how to use IoT in designing systems to produce train locations information and how this can help improve the safety of train operations. The originality in this research is exploration of how the implementation of IoT related to train tracking has been utilized and the benefits that have been felt by each stakeholder in both countries. The UK has implemented privatization, which has positively impacted infrastructure development. In addition, Office of Rail and Road (ORR) as an independent organization in UK regulates passenger information conveyed by train and station operators. In contrast, Indonesia's infrastructure is owned by the government and managed by KAI, the passenger train and station operator for mostly intercity train. The Ministry of Transportation supervises operators, implementing regulations from construction to operations. The comparison results indicate that specific regulations, data openness, and Darwin system in UK are the factors in real-time train information provision.